Management accountants as business partners : An empirical analysis based on the theory of reasoned action - Wolf, Sebastian; Weißenberger, Barbara E.; Kabst, Rüdiger; Wehner, Sebastian; Justus Liebig University Giessen (My University, 2010)
Business practice and literature frequently advocate more business oriented roles for management accountants. The aim of this study is to examine reasons for management accountants to act as business partners and to analyze corresponding performance effects. More specifically, two research questions are investigated: (i) why do management accountants act as business partners, and (ii) are business oriented management accountants beneficial to organizations?To answer these research questions we derive a theoretical model incorporating the ideas of the theory of reasoned action. We employ covariance-based structural equation modeling and dyadic survey data gathered from German management accountants and general managers for our analyses. Empirical evidence suggests that (i) in contrast to attitude, subjective norms have an effect on whether management accountants act in a business oriented way and that (ii) business orientation of management accountants is beneficial toorganizations.
Keywords: ddc:650